2011
DOI: 10.1016/j.immuni.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase B Controls Transcriptional Programs that Direct Cytotoxic T Cell Fate but Is Dispensable for T Cell Metabolism

Abstract: SummaryIn cytotoxic T cells (CTL), Akt, also known as protein kinase B, is activated by the T cell antigen receptor (TCR) and the cytokine interleukin 2 (IL-2). Akt can control cell metabolism in many cell types but whether this role is important for CTL function has not been determined. Here we have shown that Akt does not mediate IL-2- or TCR-induced cell metabolic responses; rather, this role is assumed by other Akt-related kinases. There is, however, a nonredundant role for sustained and strong activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
330
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(353 citation statements)
references
References 50 publications
19
330
3
1
Order By: Relevance
“…Furthermore, rIL-2 supplementation during the expansion phase of the CD8 + T cell response to DC-OVA vaccination did not rescue SLEC generation, suggesting that Notch affects SLEC differentiation independently of Blimp-1. A possible mechanism by which Notch regulation of CD25 expression could affect SLEC differentiation is via modulation of T cell metabolism, as IL-2 signaling is known to regulate the activity of the Akt/mTOR pathway (52)(53)(54)(55). This possibility is in agreement with the very recent observation of Backer et al (50), who have shown reduced activation of the Akt-mTOR pathway in Notchdeficient CD8 + Te cells.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, rIL-2 supplementation during the expansion phase of the CD8 + T cell response to DC-OVA vaccination did not rescue SLEC generation, suggesting that Notch affects SLEC differentiation independently of Blimp-1. A possible mechanism by which Notch regulation of CD25 expression could affect SLEC differentiation is via modulation of T cell metabolism, as IL-2 signaling is known to regulate the activity of the Akt/mTOR pathway (52)(53)(54)(55). This possibility is in agreement with the very recent observation of Backer et al (50), who have shown reduced activation of the Akt-mTOR pathway in Notchdeficient CD8 + Te cells.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, low CD3-ITAM multiplicity is sufficient for ERK signaling, but not for proliferation. Moreover, Akt is not required for the metabolic reprogramming and proliferation of T cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mTOR can be activated by Akt-independent pathways in effector CD8 + T cells (14,25), and deletion of Pten does not cause significant defects in memory formation (23). Here we circumvented the requirements of mTOR signaling in naïve T-cell homeostasis (27)(28)(29) and immediate TCR activation (10), by specific ablation of Tsc1 in antigen-experienced CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whether mTOR or the canonical activator Akt impacts memory T-cell differentiation via metabolic pathways or other pathways such as cell migration is unclear (24). Of note, Akt regulates the differentiation and function of effector CD8 + T cells via orchestrating the transcriptional program instead of cellular metabolism (25). Therefore, the upstream and downstream mechanisms for mTOR-dependent regulation of memory generation remain to be defined.…”
Section: Significancementioning
confidence: 99%